2022
DOI: 10.1002/cjoc.202200435
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Asymmetric Transformations of Unactivated Alkanes and Cycloalkanes through Direct C—H Functionalization

Abstract: The direct conversion of unactivated alkanes and cycloalkanes into structurally diverse molecules through aliphatic C-H functionalization is a useful process, which has attracted intense interest from academia and industry. Methods to control chemo-and site-selectivity, combined with asymmetric catalysis, provide appealing access to high value-added enantiomer-enriched compounds but are far less developed. This review focuses on recent progress in (i) asymmetric reactions of alkanes or cycloalkanes with prochi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…On the basis of these experiments and our previous experience, [42][43][44][45] a plausible reaction mechanism is proposed and is shown in Scheme 4a. The photocatalyst (PC1) is first excited to a triplet state (PC1*) by irradiation.…”
Section: Mechanism Proposalmentioning
confidence: 68%
“…On the basis of these experiments and our previous experience, [42][43][44][45] a plausible reaction mechanism is proposed and is shown in Scheme 4a. The photocatalyst (PC1) is first excited to a triplet state (PC1*) by irradiation.…”
Section: Mechanism Proposalmentioning
confidence: 68%
“…In the past decade, metal halide perovskites have been widely used in solar cells, light-emitting diodes, sensors and lasers due to their excellent photoelectric properties and facile assembly process. [1][2][3][4][5][6] In addition to the excellent photovoltaic effect in solar cells, metal halide perovskites also have become highly desirable candidates for luminescent materials due to high defect tolerance, adjustable band gap and emission position in the whole visible-light range, and high PLQYs. [7][8][9] As a classical three-dimensional (3D) perovskite, APbX 3 (A = Cs + , CH 3 NH 3 + , CH(NH 2 ) + ) have unique advantages of narrow full width at half-maximum (FWHM), wide color gamut and near-unity PLQY.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by these studies and our previous research on photochemical synthesis, 19,20 we chose to investigate if employing Selectfluor® as a multifunctional reagent would enable the photochemical activation of strong C(sp 3 )–H bonds, further single-electron oxidation and combination with different N -centered nucleophiles. Such a process would allow us to develop a versatile and general platform for C–N bond formation without the requirement for transition metal catalysts or external photosensitizes (Scheme 1b).…”
mentioning
confidence: 99%
“…15 Lei et al reported that photochemical Minisci-type C(sp 3 )-H arylation of alcohols and cycloalkanes with heteroarenes are promoted by Selectfluor s via hydrogen atom transfer (HAT) pathways, 16,17 and Chupakhin et al developed a blue lightpromoted C(sp 2 )-H azolation reaction of nonaromatic 2Himidazole 1-oxides mediated by Selectfluor s . 18 Inspired by these studies and our previous research on photochemical synthesis, 19,20 we chose to investigate if employing Selectfluor s as a multifunctional reagent would enable the photochemical activation of strong C(sp 3 )-H bonds, further single-electron oxidation and combination with different N-centered nucleophiles. Such a process would allow us to develop a versatile and general platform for C-N bond formation without the requirement for transition metal catalysts or external photosensitizes (Scheme 1b).…”
mentioning
confidence: 99%
See 1 more Smart Citation